Structural Analysis of Huaguangtan Arch Dam Based on Data Assimilation Parametric Inversion - LIN Xianzhi; LUO Zenghong; XU Zheng; MIN Jiesheng; CAO Chuanbo; ZHAO Quan (Renmin Zhujiang)
Aiming at the difficulty of the accurate safety assessment of the overall structural state of Huaguangtan Arch Dam,a finite element model of the arch dam is established,and the data assimilation algorithm is used to invert the material parameters based on the results of the sensitivity analysis of the mechanical parameters of the arch dam concrete and bedrock.Finally,the material parameters of finite element calculation are calibrated by parameter inversion results.The results show that the residual between the finite element displacement simulation result and the monitoring data conforms to the Gaussian distribution,and its standard deviation after data assimilation parametric inversion is reduced by 81.2%,which improves the accuracy of finite element calculation.This method enables automated operation and provides a reasonable and reliable new idea for the structural safety assessment of arch dams.